Development of STEM-Based Chemistry Textbooks to Improve Students' Problem Solving Skills - Rohmat Hidayatulloh; S. Suyono; Utiya Azizah (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2020)
This study aimed to develop STEM-based chemistry textbooks on reaction rate topic, in order to improve students' problem solving skills. Textbooks are developed using the Research & Development (R&D) scheme with feasibility indicators seen from the validity and effectiveness of textbooks. The developed textbook was then tested using a one group pretest-postest design research, where the research subjects were 30 students of class XI at SMA Wachid Hasyim 1 Surabaya. The research data were obtained from expert validation sheets and student problem solving skills test sheets. Based on the research conducted, it was found that 1) the textbook developed had a validity score of 3.70 and was categorized as very valid, 2) the increase in student problem solving skills classically obtained was 0.75, in the high category, 3) the percentage of completeness a test of student problem solving skills by 90%, so that STEM-based textbooks can be state to be effective in improving students' problem solving skills. Based on these results, it can be conclude that STEM-based textbooks developed feasible to improve students' problem solving skills.